2018
DOI: 10.32947/ajps.v18i2.478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of General and Spinal Anesthesia on Hepatic and Renal functions and Hemodynamic parameters of Iraqi Women Undergo Cesarean Section: Comparative Study

Abstract: Both general and spinal anesthesia can be use during caesarean section. Spinal anesthesia is preferred by anesthesiologists and gynecologists because of its beneficial effects for both mothers and their fetuses. They were not affecting the creatinine level but affecting only on elevation of liver enzymes. Spinal anesthesia effect on hemodynamic parameters more than general anesthesia, and it causes less operative blood loss than general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…In our study, the result showed that core body temperature was not statistically significant between treatment sub-groups (Table 2; P= 0.107) which was consistent with the result of Vasanthy.j et al (25). However, the study of Igweagu et al (26) and Matsukawa et al (27) showed the core body temperature of participants was decreased after anesthesia. Our result showed that the incidence of shivering was 21.59% in participants which was 31.34% in participants who received no intervention, warmed cover, and fluid therapy; and 18.05% in participants who received tramadol, pethidine, or clonidine.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the result showed that core body temperature was not statistically significant between treatment sub-groups (Table 2; P= 0.107) which was consistent with the result of Vasanthy.j et al (25). However, the study of Igweagu et al (26) and Matsukawa et al (27) showed the core body temperature of participants was decreased after anesthesia. Our result showed that the incidence of shivering was 21.59% in participants which was 31.34% in participants who received no intervention, warmed cover, and fluid therapy; and 18.05% in participants who received tramadol, pethidine, or clonidine.…”
Section: Discussionsupporting
confidence: 87%
“…According to our findings, the reduced incidence of liver injury following isoflurane may be explained by the drug's lower metabolism and superior preservation of hepatic blood flow [11]. Most surgical procedures are monitored with small changes in liver function tests, regardless of whether they are conducted under regional (epidural or spinal) or general anaesthesia [15]. During all surgical operations, anaesthesia lowers blood flow to the liver.…”
Section: Discussionmentioning
confidence: 77%
“…Prior research shows that anesthetic drugs, such as propofol and fentanyl, have an effect on the central nervous system and also on the endocrine and immune inflammatory system, attenuating the release of various types of cytokines and catecholamines into the blood flow and thus conferring protection on the immune reaction triggered by the endoscopic procedure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%